2012
DOI: 10.1111/j.1463-1318.2011.02817.x
|View full text |Cite
|
Sign up to set email alerts
|

Palliative excisional surgery for primary colorectal cancer in patients with incurable metastatic disease. Is there a survival benefit? A systematic review

Abstract: The studies indicate that there may be a survival benefit for primary resection of colorectal cancer in stage IV disease. The findings suggest that resection of the primary tumour should be based on tumour burden and performance status rather than on the presence or absence of symptoms alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 51 publications
1
40
2
Order By: Relevance
“…Surgical resection is the mainstay of therapy in locoregional and eligible metastatic colorectal cancer (9). Colectomy, low anterior excision, or abdominoperineal resection may be performed through laparoscopic or open surgery for the patients with colorectal cancer (10,11).…”
Section: Contextmentioning
confidence: 99%
“…Surgical resection is the mainstay of therapy in locoregional and eligible metastatic colorectal cancer (9). Colectomy, low anterior excision, or abdominoperineal resection may be performed through laparoscopic or open surgery for the patients with colorectal cancer (10,11).…”
Section: Contextmentioning
confidence: 99%
“…Primary resection, however, has been shown to confer a significantly longer overall survival than patients managed only with chemotherapeutics [80]. A recent study by Anwar et al suggests that prognostic factors such as tumor burden and performance status, should dictate the necessity for surgical resection rather than the presence of symptoms [9]. Results of a meta-analysis by Stillwell, Buettner and Ho suggest disabling symptoms that arise from the primary tumor as it progresses, including weight loss, pain, nutritional depletion, and anemia/hemorrhage may be prevented by resection of the primary lesion.…”
Section: Surgical Management Of Primary Tumormentioning
confidence: 99%
“…Despite advances to include more patients into the "curative" resection group, the most common treatment of stage IV CC remains palliative colon resection conducted primarily to prevent complications such as obstruction, perforation and hemorrhage [9,83]. It is suggested that resection of the primary may also confer an overall survival benefit.…”
Section: Surgical Management Of Primary Tumormentioning
confidence: 99%
See 2 more Smart Citations